Persepsi Mahasiswa Ilmu Ekonomi dan Keuangan Islam Terhadap Pembelajaran Bahasa Arab - Syammaz Az Zayadarach Yusra; Mohamad Sirojul Fikri; Najwa Huzaifah; Insani Najwa Qotrunnida (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Student perceptions are an important part of determining learning design, learning methods, and so on. The purpose of this research is to examine students' perceptions of Arabic language learning. The study was carried out descriptively using quantitative descriptive research methods. Survey techniques were chosen to obtain data from this research. The population was taken using a voluntary sampling technique consisting of students from the Islamic Economics and Finance study program at the Indonesian Education University who had taken or were currently taking Arabic language courses. The data obtained was analyzed using a descriptive statistical approach. Analysis using this approach was carried out to determine the frequency of respondents' answers and their percentages. The research results show that students' perceptions of Arabic language learning are relatively good. However, Arabic is considered a difficult subject.